Dynamic optimized cooperation in multi‐source multi‐relay wireless networks with random linear network coding - Benamira, E.; Merazka, F.; Kurt, G. K. (Electronics letters, 2021)
The authors present a strategy that improves the reliability of data transmission from multiple sources towards a destination D via multiple relays over wireless channels. After the broadcast phase, the destination selects the best cooperative direct link sources with the highest instantaneous signal‐to‐noise ratio γ, then generates and sends the random linear network coding coefficient matrix to the relays. After receiving the random linear network coding–coded symbols (packets) from the relays, D completes the reception and decoding of all source nodes packets. Monte Carlo simulations are conducted with Galois field (GF) (q) symbols (q = 2, 4 and 8) and the results are compared with the scenario of static cooperative direct links. An important decrease of symbol error rate (SER) is achieved. Furthermore, the efficiency of this approach is confirmed for the whole range of possible values of path loss exponent on direct links, that is, all types of environment between source nodes and destination D.